PERILAKU DESTRUKTIF WATANABE SHUUYA DALAM FILM KOKUHAKU - KURNIAWATI, CHRISTINE (Jurnal Ilmiah Mahasiswa FIB, 2013)
Destructive behavior is a behavior which is affected from the death drive thatmakes someone wants to destroy everything around them including themselves.Watanabe Shuuya, main character of Kokuhaku as the main object of this study hasbeen analyzed mainly wit h Freud’s psychoanalyt ic for his destructive behavior. Besideusing psychology’s theory, sociology’s theory has been used to analyze because of therelation between this film and the reality in Japan. Therefore, there are two problemsthat have been solved for this study, namely: (1) What is Watanabe Shuuya’s motive ofhis destructive behavior and what is Watanabe Shuuya’s character, and (2) HowWatanabe Shuuya’s psychology pheno mena related with the reality in Japan.This study was using psychosocial literature. From the psychological problem, Freud’s psychoanalyt ic has been used to analyze character’s unconscious behavior.From the sociological problem, report of Japan’s observers which is related with thisstudy has been used to analyze the relation between the film and reality. The result ofthe study has been proved by some character’s dialogs and some screenshots of the film.As the results, there are 16 unconscious behaviors of Watanabe Shuuya. 3 of Watanabe Shuuya’s unconscious behavior is destructive behaviors which is desire oreven act to kill, desire to suicide, and idea to make a destructive thing. Motive of thisdestructive behaviors are some acts that come from his desire to be loved by his mother,his emotional state and his despair. Related with the motives, Watanabe Shuuya’scharacter is dominant with id so he become an impulsive man who shows all his feelingwith his destructive behavior. The similarity of this film and the reality in Japan ismot ive of the destructive behavior in this film and juvenile crime’s mot ives in Japan. Keywords : destructive behavior, death drive, Kokuhaku, Freud’s psychoanalytic